Safety and efficacy of angiotensin receptor neprilysin inhibitor in improving cardiac function and blood pressure in dialysis patients - Zhou, Kai; Zhang, Qiuyue; Dong, Wen; Li, Xin; Sun, Yimiao; Zhang, Ying (Frontiers in Medicine, 2024)
Background The efficacy of the angiotensin receptor neprilysin inhibitor (ARNI) sacubitril/valsartan (SV) in patients with chronic kidney disease (CKD) has been established. Two meta-analyses have demonstrated its significant role in enhancing ventricular remodeling. However, the effectiveness and safety of its use in patients with end-stage renal disease (ESRD) remain unclear. Methods and results Up to October 2023, we searched the PubMed, Embase, and Web of Science databases for studies involving ESRD patients treated with ARNI. The quality of the included studies was evaluated using the Newcastle-Ottawa Scale. Effect sizes were reported as mean differences (MD) with 95% confidence intervals (CIs). We included 10 studies, encompassing 649 patients. ARNI was associated with improvements in blood pressure and left ventricular (LV) function in ESRD patients, including systolic blood pressure (SBP) (MD −12.76 mmHg; 95% CI, −18.03 to −7.5 mmHg), diastolic blood pressure (DBP) (MD −6.41 mmHg; 95% CI, −8.10 to −4.72 mmHg), and left ventricular ejection fraction (LVEF) (MD, 4.61%; 95% CI, 1.78%−7.44%). Hemoglobin levels improved, but there were no significant statistical differences in other biomarkers for dialysis. Sacubitril/valsartan was generally well tolerated in ESRD patients. Improved indices of left ventricular function were noted at 6 months and were more pronounced at 12 months. A linear relationship between LVEF and left ventricular end-diastolic volume (LVEDV) was observed, as indicated by a high correlation coefficient (r-value). Conclusion ARNI effectively reduces blood pressure and enhances left ventricular function in dialysis patients, with early treatment associated with greater benefits. ARNI also demonstrates a favorable safety profile in this population. Further prospective studies are required to fully understand the long-term efficacy and safety of sacubitril/valsartan in dialysis patients.